Impact of stent design on in-stent stenosis in a rabbit iliac artery model - Sommer, Christof-Matthias; Grenacher, Lars; Stampfl, Ulrike; Arnegger, Florian; Rehnitz, C.; Thierjung, Heidi; Stampfl, Sibylle; Berger, I.; Richter, Götz Martin; Kauczor, Hans-Ulrich; Radeleff, Boris (CardioVascular and interventional radiology, 2010)
The purpose of this study was to evaluate the impact of stent design on in-stent stenosis in rabbit iliac arteries. Four different types of stent were implanted in rabbit iliac arteries, being different in stent design (crown or wave) and strut thickness (50 or 100 microm). Ten stents of each type were implanted. Each animal received one crown and one wave stent with the same strut thickness. Follow-up was either 12 weeks (n = 10 rabbits) or 24 weeks (n = 10 rabbits). Primary study end points were angiographic and microscopic in-stent stenosis. Secondary study end points were vessel injury, vascular inflammation, and stent endothelialization. Average stent diameter, relative stent overdilation, average and minimal luminal diameter, and relative average and maximum luminal loss were not significantly different. However, a trend to higher relative stent overdilation was recognized in crown stents compared to wave stents. A trend toward higher average and minimal luminal diameter and lower relative average and maximum luminal loss was recognized in crown stents compared to wave stents with a strut thickness of 100 microm. Neointimal height, relative luminal area stenosis, injury score, inflammation score, and endothelialization score were not significantly different. However, a trend toward higher neointimal height was recognized in crown stents compared to wave stents with a strut thickness of 50 microm and a follow-up of 24 weeks. In conclusion, in this study, crown stents seem to trigger neointima. However, the optimized radial force might equalize the theoretically higher tendency for restenosis in crown stents. In this context, also more favorable positive remodeling in crown stents could be important.